Successful HLA-identical sibling cord blood transplantation in a 6-year-old boy with leukocyte adhesion deficiency syndrome - Starý, J; Bartůnková, J; Kobylka, P; Vávra, V; Hrusák, O; Calda, P; Král, V; Svorc, K (Bone marrow transplantation, 1996)
A 6-year-old boy with the severe form of the leukocyte adhesion deficiency syndrome (LAD) received a transplant of cord blood (CBT) from his HLA-identical brother. The donor was proved healthy by successful prenatal diagnosis. CBT was performed after conditioning with etoposide, busulfan and cyclophosphamide. After hematopoietic recovery complete chimerism was proved as well as the normal expression of CD11x/CD18 complex on circulating leukocytes. The only post-transplant complication was a mild pneumonitis resolving on the corticosteroid therapy. Thirteen months after CBT the boy is in good health and shows no signs of immunodeficiency. As far as we know this is the first report of successful CBT in a patient with LAD syndrome.
Keywords: nemoci plodu; Chimera; nukleární rodina; dítě; novorozenec; fetální krev; Fetal Diseases; histokompatibilita; lidé; Hematopoietic Stem Cell Transplantation; Infant, Newborn; Nuclear Family; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; Transplantation Conditioning; Immunophenotyping; Fetal Blood; imunofenotypizace; Histocompatibility; Male; Cordocentesis; Leukocyte-Adhesion Deficiency Syndrome; chiméra; LAD syndrom; Child; mužské pohlaví; odběr fetální krve; Humans